Giant voltage generating microcantilevers based on Ba0.85Ca0.15Zr0.1Ti0.9O3 and Co76Fe14Ni4Si5B for next-generation energy harvesters. (15th April 2020) - Kumar, Ajith S.; Lekha, C.S. Chitra; Vivek, S.; Anantharaman, M.R.; Saravanan, K. Venkata; Nair, Swapna S.
Abstract: Magnetoelectric thin-film heterostructures with piezoelectric Ba0.85 Ca0.15 Zr0.1 Ti0.9 O3 and magnetostrictive Co76 Fe14 Ni4 Si5 B are fabricated. Very high ME coupling coefficients of 8 V/(cm Oe) and 5.8 V/(cm Oe) are observed for BCZT-MG-BCZT and MG-BCZT-MG trilayers at sub resonance. Micro cantilevers of multilayers with total thickness of 130 µm are also fabricated. The microcantilever of BCZT-MG-BCZT showed an enhanced resonance at a frequency of 840 Hz with MECC as high as 1457 V/(cm Oe). These structures can be effectively employed as an active component in energy harvesters, sensors, and transducers due to their exceptional ME responses in the resonant and sub-resonant frequencies. Graphical abstract: Image, graphical abstract